Analysis of Parental Involvement in Parenting Programmes: A Case Study in Public Elementary School 2 Kemasan Boyolali - Dicky Dermawan, Deden; Fauziah, Puji Yanti (Elementary Teacher Education Program, Majalengka University, 2025)
Parenting programmes in elementary schools play an important role in supporting students' character development but often face challenges in terms of parental involvement. Problems include low parental participation in school activities, limited resources and parents' lack of understanding of their role in their children's education. The purpose of this study was to identify the role of parents in students' character development, the challenges faced in implementing the parenting programme, as well as the strategies implemented by the school to increase parental participation in public school 2 Kemasan, Boyolali, Indonesia. This study used qualitative methods with direct observation techniques, structured interviews with parents, teachers, and principals, and document analysis related to the parenting programme. The results show that despite constraints such as limited time and resources, active parental involvement can improve students' attitudes, discipline and learning motivation. However, the level of parental participation in some activities is still low, which affects the effectiveness of the programme. Recommendations to improve the effectiveness of the parenting programme include providing parenting materials online to overcome time constraints and collaborating with external counsellors to provide more support to parents in educating their children. This research is expected to provide insights for other schools in optimising their existing parenting programmes.